Ichthyoplankton DNA metabarcoding as a tool for large-scale inventory and reproductive dynamics analysis of the ichthyofauna - Daniel Fonseca Teixeira (2024)
The study of ichthyoplankton is paramount to understand the reproductive dynamics of local fish assemblages, but its morphological identification is often challenging even to experienced taxonomists. Despite being a powerful tool for assertive taxonomic identification, DNA barcoding becomes too expensive and laborious in large-scale inventories. DNA metabarcoding can overcome these limitations as a rapid, cost-effective, broad and accurate taxonomy alternative for the identification of multiple individuals simultaneously, but the standardization of accessible and efficient protocols still poses a challenge for its recurrent usage. With that in mind, we applied the DNA metabarcoding method to identify ichthyoplankton samples collected at the area impacted by the Três Marias reservoir, São Francisco River Basin, Southeastern Brazil. Using molecular identification, we aim to elucidate four major questions: (a) can 12S rRNA gene minibarcode markers MiFish and NeoFish detect and identify the sampled species as accurately as the COI gene marker standardized for DNA barcoding, using next generation sequencing (NGS)? (b) what is the relative contribution of eggs and larvae to total observed richness? (c) is there significant difference between upstream and downstream Três Marias ichthyoplankton communities? (d) should any studied tributary be considered as a conservation priority hotspot? Overall, our results suggest that the minibarcode markers can be as efficient as COI for species detection, when a reliable and complete database is available. Furthermore, despite the statistical insignificant and low differentiation found between upstream and downstream ichthyoplankton communities, only in the Paracatu River, located downstream from the reservoir, all the greater migratory species were detected, highlighting this tributary as a primary hotspot for conservation. Therefore, this study aims at contributing not only by enhancing large-scale and precise inventory techniques, but also by elucidating issues about the fish reproductive dynamics in the area impacted by Três Marias reservoir that are pivotal for guiding ichthyofauna conservation and management.